Oxidative stress induces senescence and sterile inflammation in murine amniotic cavity - Polettini, Jossimara [UNESP]; Richardson, Lauren S.; Menon, Ramkumar (Elsevier, 2018)
Objective: A physiologic increase of reactive oxygen species (ROS) is observed through pregnancy. ROS-induced damage to major cellular elements, specifically protein peroxidation, can lead to fetal and placental tissue senescence and inflammation often associated with normal parturition. The purpose of this study was to examine the effects of oxidative stress (OS) in inducing changes in proteins, senescence, and sterile inflammation in pregnant mice. Methods: CD-1 mice (n = 5/group) on day 14 of gestation were subjected to minilaparotomy and the uterine horn between gestational sacs was injected with the following: saline (control), cigarette smoke extract (CSE) CSE diluted in saline and CSE + SB 203580 (SB) (a p38 mitogen-activated protein kinase (MAPK) inhibitor). Mice were sacrificed on day 18, and amniotic sacs, placentas and amniotic fluid (AF) were collected. Protein damage was evaluated by immunostaining for 3-Nitrotyrosine modified proteins (3-NT). Activation of prosenescence p38MAPK was evaluated by western blot. Senescence features, β-galactosidase (SA-β−Gal) and AF inflammatory cytokines were analyzed by immunostaining and multiplex luminex-based immunoassays, respectively. The data were analyzed by ANOVA and Tukey's test, p <.05 was used for significance. Results: Amniotic sac from CSE-treated animals showed significant protein peroxidation compared to control as indicated by 3-NT staining. CSE activated p38MAPK phosphorylation in amniotic sac but not in placenta. Membrane p38MAPK activation was reduced after treatment with SB. CSE increased fetal membrane senescence (staining for SA-β−Gal) and increased AF concentrations of all evaluated cytokines. High inflammation correlated with pup loss and a decrease in placental weight. Treatment with p38MAPK inhibitor (SB) minimized damages, senescence and sterile inflammation. Conclusion: OS induction by cigarette smoke extract cause fetal tissue protein damage, p38MAPK activation, senescence and sterile inflammation in the amniotic cavity of mouse. Prevention of p38MAPK activation can be a novel approach to prevention of adverse pregnancy outcomes related to OS induced premature senescence.
Keywords: Cigarette smoke; Fetal membranes; Inflammation; Labor; Murine model; p38MAPK; Protein damage